Історико-правовий аспект розбудови державного управління у Волинському воєводстві - Пащук, Т.; Pashchuk, T. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті проведено комплексне вивчення процесів і явищ, пов’язаних зі становленням, організацією та головними напрямами діяльності державного управління у Волинському воєводстві міжвоєнного періоду. Польська влада міжвоєнного періоду в ставленні до українців керувалася засадами забезпечення цілісності держави й блокування автономічних прагнень українців, гарантування полякам домінування, придушення будь-яких антидержавних замахів, пошуки порозуміння на умовах асиміляції українців і визнання ними територіальної цілісності Польщі.The article conducts a comprehensive study of processes and phenomena associated with the formation, organization and main lines of activity of the state administration in the Volyn Province of the interwar period. On the basis of investigations of national scientists and Polish researchers’ evidences the separation of government of II Rich Pospolyta in the interwar period, the structure of the Provincial Office and the individuals of governors were found out, the power and authority of Volyn’ state power were traced, and social groups of the Province who joined the ranks of officials were investigated. It is indicated that for the effective leadership of Volyn province the higher level of the government hierarchy was occupied by persons of Polish origin, Poles – natives of Ukraine and persons, who were loyal to the Polish authorities.
The Historically-legal Aspect of Development of State Administration in the Volyn Province.
Keywords: Друга Річ Посполита; міжвоєнний період; воєводи; Second Rich Pospolita; intermilitary period; voevodes